Final year project student to supervisor distribution and abstract text analysis system - Mohd Azwan Md Saad (2019)
Final Year Student to Supervisor Distribution and Abstract Text Analysis is proposed as a system to allocate student to supervisor and analyse student's abstract. In Faculty Informatics and Computing program run by University Sultan Zainal Abidin (UniSZA), student are required to develop a software prototype and write a proposal for their final project. In order to start their project, a group of student will assigned under a supervisor. Faculty management responsible to allocate student with supervisor. There are several weakness on current procedure when allocating supervisor to student which is some lecturers do not get a balanced CGPA's student in the group. Then students do not have supervisors in accordance with their expertise to assist in the project to be done. Supervisor also, difficult to recognize either the title suggest already taken by previous student or not. This System will be able to divide the group fairly, student can get their needed supervisor expertise and the proposal will compared with previous to make sure the project different and new. This system using TF-IDF (Term frequency-inverse document frequency) and priority method. Therefore, this system uses web based platform that has been developed and will solve the faculty management problem, and ease the student.